Auditor tolerance of accrual-based and real earnings management in boardrooms of politically connected Nigerian firms - Salau Abdul Malik; Ayoib Che Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examines the accrual-based and real earnings management tolerance of auditors in boardrooms of politically connected companies using auditor reputation theory and auditor litigation risk as the theoretical framework. Using a sample of 89 Nigerian listed companies during the period from 2008 to 2013, the study finds that auditors tolerate more accrual earnings management and less real earnings management in companies that are politically connected. In addition, the study finds a complementary relationship between real earnings management (REM) and abnormal earnings management (ABD) in companies that are politically connected. The findings of this study have serious implications for regulators, particularly following the various corporate governance scandals that have affected the integrity of financial information.